2013
DOI: 10.1002/jbm.b.33048
|View full text |Cite
|
Sign up to set email alerts
|

Metal release and speciation of released chromium from a biomedical CoCrMo alloy into simulated physiologically relevant solutions

Abstract: The objective of this study was to investigate the extent of released Co, Cr(III), Cr(VI), and Mo from a biomedical high-carbon CoCrMo alloy exposed in phosphate-buffered saline (PBS), without and with the addition of 10 µM H2 O2 (PBS + H2 O2 ), and 10 g L(-1) bovine serum albumin (PBS + BSA) for time periods up to 28 days. Comparative studies were made on AISI 316L for the longest time period. No Cr(VI) release was observed for any of the alloys in either PBS or PBS + H2 O2 at open-circuit potential (no appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 42 publications
(118 reference statements)
6
46
0
1
Order By: Relevance
“…A small, but statistically significant Cr enrichment and Co depletion was also observed for disks exposed to PBS + BSA (nonirradiated) as compared to PBS (both nonirradiated and irradiated), Figure (a). This is also in agreement with previous observations . Mo was statistically significant enriched in PBS + BSA as compared to PBS (for irradiated disks), Figure (a).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…A small, but statistically significant Cr enrichment and Co depletion was also observed for disks exposed to PBS + BSA (nonirradiated) as compared to PBS (both nonirradiated and irradiated), Figure (a). This is also in agreement with previous observations . Mo was statistically significant enriched in PBS + BSA as compared to PBS (for irradiated disks), Figure (a).…”
Section: Resultssupporting
confidence: 93%
“…Upon immersion in all solutions for one hour, the surface oxide became enriched in Cr. This enrichment (coupled with a Co depletion) is expected from earlier studies . A small, but statistically significant Cr enrichment and Co depletion was also observed for disks exposed to PBS + BSA (nonirradiated) as compared to PBS (both nonirradiated and irradiated), Figure (a).…”
Section: Resultssupporting
confidence: 82%
“…These findings are in agreement with previous chromium speciation measurements for released chromium from chromium-containing alloys in synthetic biological fluids (Flint et al, 2007;Hedberg et al, 2013;Hedberg and Odnevall Wallinder, 2014).…”
Section: Resultssupporting
confidence: 94%
“…Interestingly, chromium is present in both the stainless steel and CoCrMo alloys that were frequently retrieved. It is known that CoCrMo alloy implants corrode and release both chromium and cobalt ions . Finally, we found that the reasons for primary and revision surgery were comparable with registered information from the nationwide Danish Hip Arthroplasty Register (Tables and ), but acknowledge that a major proportion of these were categorized as ‘unknown’.…”
Section: Discussionsupporting
confidence: 68%